Assessing health-related quality of life in patients with heart failure: a systematic, standardized comparison of available measures. - Garin, O; Herdman, M; Vilagut, G; Ferrer, M; Ribera, A; Rajmil, L; Valderas, J; Guillemin, F; Revicki, D; Alonso, J (2014)
To systematically evaluate available health-related quality of life (HRQL) instruments for use in patients with heart failure (HF). Seven HF-specific HRQL questionnaires and associated studies of their metric properties were identified by systematic review: the Chronic Heart Failure Assessment Tool, the Cardiac Health Profile congestive heart failure, the Chronic Heart Failure Questionnaire (CHFQ), the Kansas City Cardiomyopathy Questionnaire (KCCQ), the Left Ventricular Disease Questionnaire (LVDQ), the Minnesota Living with Heart Failure Questionnaire (MLHFQ), and the Quality of Life in Severe Heart Failure Questionnaire. Each instrument was assessed by four experts using a standardized tool for evaluating patient-reported outcomes (EMPRO; scores from 0 to 100). Four questionnaires were given adequate scores (median >50) for the attribute "conceptual model." The LVDQ had the highest rated median for "reliability" (72.8). The CHFQ, the KCCQ, and the MLHFQ all got reasonable scores for "validity" (from 54.4 to 76.4). The reviewers rated the KCCQ the highest in terms of "sensitivity to change" (median 94.4). Only the CHFQ (50.0) and the KCCQ (72.2) received adequate scores for the "interpretability" attribute. The most highly rated instruments based on the overall EMPRO score were the KCCQ (64.4) and the MLHFQ (60.7), followed by the CHFQ (59.2). Based on the first systematic and reliable expert-based evaluation of available HF-specific HRQL questionnaires, the evidence seems to support the choice of the KCCQ, the MLHFQ, and the CHFQ over the others, which require further research on metric properties.